(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nurvianto S, Adrianti DT, Hamdan F, Triyanto J, Darmanto A. 2022. Population density survey of white-bearded gibbons (Hylobates albibarbis) in high conservation value forest area of palm oil plantation company, Central Kalimantan, Indonesia. Biodiversitas 23: 2245-2254. Bornean white-bearded gibbon (Hylobates albibarbis Lyon, 1911) or Bornean agile gibbon or southern gibbon is an endemic primate of Borneo and its distribution is limited to the forest areas in Central Kalimantan and West Kalimantan, Indonesia. However, its habitat is not restricted to the natural and undisturbed forest because this species also utilizes some forest blocks around rubber and palm oil plantation as habitats. This study aimed to estimate this species’ population density and distribution in the five conservation blocks of PT Sawit Sumbermas Sarana (PT SSS), Indonesia and identify factors affecting its distribution. A field survey was conducted in five high conservation value forest areas inside the PT SSS management area, namely Pondok Duku Block, East Bravo Rangda Block, West Bravo Rangda Block, Tanjung Biru Block, and forest blocks around Kenambui Lake. Data was collected from April to May 2019 using the auditory sampling method through predetermined fixed Listening Posts (LP) to record population data. In addition, the protocol sampling technique was employed to systematically record the habitat features within the research site by establishing 0.04 ha plots systematically with a distance between plots of 400 m. Factors affecting gibbon distribution were identified using binary logistic regression. From the field survey, we identified that the southern gibbon was only found in East Bravo Rangda Block and Tanjung Biru Block with a population density of 4.26 ± 0.12 group/km² or 8.53 ± 0.34 individual/km² and 4.26 ± 0.12 group/km² or 8.53 ± 0.34 individual/km², respectively. Gibbon distribution was significantly associated with the number of seedlings (0.024±0.010, P=0.015), saplings (0.128±0.042, P=0.002), and trees (0.225±0.110, P=0.042. This result showed that vegetation condition strongly influences the presence of gibbon in an area.